2018
DOI: 10.1038/s41386-018-0261-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction: ApoE2 Exaggerates PTSD-Related Behavioral, Cognitive, and Neuroendocrine Alterations

Abstract: Following the publication of this article the authors noted an error in Fig. 4. In sub-panels D-F, the y-axis should read "apoE (ng/ mg protein)" as opposed to "apoE (ng/ml)". The authors apologize for any inconvenience caused. The correct version of figure 4 is shown below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With respect to neuropsychiatric associations a single small study found that e2 promoted risk for post-traumatic stress disorder (PTSD) ( Johnson et al, 2019 ). Further studies were negative as was a meta-analysis ( Roby, 2017 ), suggesting this was an exemplar of the “winner’s curse.” No studies have been published in the area of e2 associations with personality traits.…”
Section: Apoe E2 Pleiotropy For Riskmentioning
confidence: 99%
“…With respect to neuropsychiatric associations a single small study found that e2 promoted risk for post-traumatic stress disorder (PTSD) ( Johnson et al, 2019 ). Further studies were negative as was a meta-analysis ( Roby, 2017 ), suggesting this was an exemplar of the “winner’s curse.” No studies have been published in the area of e2 associations with personality traits.…”
Section: Apoe E2 Pleiotropy For Riskmentioning
confidence: 99%